DNA repair enzymes in sunscreens and their impact on photoageing—A systematic review - Luze, Hanna (Photodermatol Photoimmunol Photomed, 2020)
BACKGROUND: DNA damage is one of the main factors responsible for photoageing and is predominantly attributed to ultraviolet irradiation (UV‐R). Photoprotection by conventional sunscreens is exclusively prophylactic, and of no value, once DNA damage has occurred. As a result, the demand for DNA repair mechanisms inhibiting, reversing or delaying the pathologic events in UV‐exposed skin has sparked research on anti‐photoageing and strategies to improve the effect of conventional sunscreens. This review provides an overview of recent developments in DNA repair enzymes used in sunscreens and their impact on photoageing. METHODS: A systematic review of the literature, up to March 2019, was conducted using the electronic databases, PubMed and Web of Science. Quality assessment was carried out using the Newcastle‐Ottawa scale (NOS) to ensure inclusion of adequate quality studies only (NOS > 5). RESULTS: Out of the 352 publications, 52 were considered relevant to the key question and included in the present review. Two major enzymes were found to play a major role in DNA damage repair in sunscreens: photolyase and T4 endonuclease V. These enzymes are capable of identifying and removing UV‐R‐induced dimeric photoproducts. Clinical studies revealed that sunscreens with liposome‐encapsulated types of photolyase and/or T4 endonuclease V can enhance these repair mechanisms. CONCLUSION: There is a lack of randomized controlled trials demonstrating the efficacy of DNA repair enzymes on photoageing, or a superiority of sunscreens with DNA repair enzymes compared to conventional sunscreens. Further studies are mandatory to further reveal pathogenic factors of photoageing and possible therapeutic strategies against it.